Canciones infantiles para el desarrollo del lenguaje oral de los niños de Educación Inicial II - Donoso Ruiz, Kleber Adrian (2025)
Nursery rhymes are important for the oral language development of children in early childhood education. Nursery rhymes allow children to acquire new linguistic skills, recognize and associate new words with existing words, as well as help in pronunciation, recognize sounds and manage a rhythm of words appropriate for their growth, highlighting what is fundamental for the development of oral language. The objective of this study is to understand, analyze and detail the children's songs for the development of oral language of the children of Initial Education II in the School of Basic Education “Arcadio Soto Santana” of the Vinces canton. In which it could be observed that the established problem is detailed through descriptive research, in which deductive and inductive methods are based for a better understanding, with a non-experimental design and a qualitative approach that allow the execution of the present research study. The results of the research show benefits that children acquire through children's songs in it are oral expression, language development, language comprehension, communication, pronunciation, gestural expression and socialization, as a conclusion it is detailed that the processes that favor the development of oral language of children influences the linguistic and oral expression that is achieved through children's songs in which they develop oral language skills.